Marine heatwaves characteristics in the Mediterranean Sea: Case study the 2019 heatwave events - Hamdeno, Manal; Alvera-Azcaráte, Aida (Frontiers in Marine Science, 2023)
Marine Heatwaves (MHWs) are considered one of the main consequences of global warming. MHWs negatively affect ecosystems, threaten economies, and intensify storms. In this work, we investigated the main characteristics of MHWs in the Mediterranean Sea from 1982 to 2020 and examined the relationship between their frequency and teleconnection patterns (e.g., East Atlantic Pattern (EAP) and East Atlantic/Western Russian Pattern (EATL/WRUS)). We then focused on the most intense MHW events that occurred in 2019 in the western Mediterranean Sea (WMB) and eastern Mediterranean Sea (EMB) by examining the link between the SST anomaly (SSTA) and various atmospheric forcings during these events. Our results showed that MHWs were more frequent and intense in the WMB than in the EMB on temporal and spatial scales, while the duration of MHWs was longer in the EMB. The trend of MHW frequency and duration in the Mediterranean Sea between 1982 and 2020 was about 1.3 ± 0.25 events/decade and 3.6 ± 1.16 days/decade, respectively. More than half of all MHW events in the Mediterranean Sea were recorded in the last decade (2011-2020). The results also showed that the EAP plays an important role in modulating MHW frequency in the Mediterranean Sea, with a strong positive correlation of 0.74, while the EATL/WRUS was strongly negatively correlated with MHW frequency in the EMB, with a correlation of about -0.60. In 2019, six MHW events were observed in the WMB, three of which were classified as strong events (SST exceeded two times the climatological threshold), while two events were detected and classified as strong events in the EMB. In the WMB, the 2019 MHWs extended to a depth of about 20 meters into the water column, while the MHWs in the EMB extended to greater depths of over 50 meters. The strong MHW events in the WMB were associated with a large positive heat flux anomaly and a shallow mixed layer. In the EMB, the high SSTA associated with MHW events caused heat loss from the ocean to the atmosphere and was associated with a shallow mixed layer and anomalously low mean sea level pressure. Finally, a negative relationship between the SSTA and surface Chl-a concentrations was observed during the 2019 MHW events. This negative influence of MHWs on Chl-a was more pronounced in the WMB than in the EMB, suggesting that the WMB MHW events were intense enough to infer a response to chlorophyll-a concentrations.